Effect of nefopam in normal chickens and its relationship to hydrogen peroxide-induced oxidative stress - Yaareb J. Mousa (Iraqi Journal of Veterinary Sciences, 2021)
The objective designated to discover the analgesic effect of nefopam in the normal (non-stressed) chickens and its possible alteration due to hydrogen peroxide (H2O2)-induced oxidative stress (OS) in 7-14 day old chickens. The analgesia of nefopam has been increased by 47% in the stressed chickens by measuring the analgesic Median Effective Dose (ED50) value. This value was 9.10 mg/kg, IM in the normal chickens where it became 4.80 mg/kg, IM in stressed chickens. There is a significant rise in the antinociceptive action of nefopam 18 mg/kg, IM by 88% in the stressed group of chickens in comparison with the normal one elicited by an electro-stimulation and formaldehyde 0.05 ml of 0.1% tests for induction of nociception. The observations showed several significant stimulatory modifications in the neurobehaviour when nefopam treated with a subtle dosage 1 mg/kg, IM in the stressed chickens concerning the latency to move, squares crossed and time of the tonic immobility response test. Significant damage was detected in the liver function when nefopam injected at 18 mg/kg, IM in stress chickens in comparison to normal one by 28, 33 and 65% as estimated through Alkaline phosphatase (ALP), Aspartate trans-aminase (AST) and Alanine trans-aminase (ALT) concentrations in the serum, respectively. The sum of data findings indicated that H2O2-inducedOS increased the analgesic activity of nefopam in the chickens; despite the changes occur on the neurobehaviour and liver function. The dose of nefopam should be reduced when preparing the therapeutic regimen in the stressed animals.